2005
DOI: 10.1136/gut.2003.017517
|View full text |Cite
|
Sign up to set email alerts
|

Association between family history and mismatch repair in colorectal cancer

Abstract: Background and aims: Germline mutations in mismatch repair (MMR) genes cause a greatly increased risk of cancer of the gastrointestinal and female reproductive tracts (hereditary non-polyposis colorectal cancer (HNPCC)). Loss of MMR expression is common in colorectal cancer (CRC) overall. Such loss is assumed to be acquired predominantly, although a population of CRC cases will include individuals with unrecognised MMR mutations. This study examines the association between MMR gene expression and family histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…As seen in other studies [4, 15, 37, 56, 67, 93, 94, 100–102], colorectal tumors with lack of MMR protein expression, suggesting MMR deficiency, were associated with a proximal location in the colon and poor histological differentiation. However, opposing previous publications [4, 17, 19, 37, 55, 72, 79, 101–104], we did not observe associations of MMR protein-negative tumors with gender, earlier age at diagnosis of cancer, positive personal and family history of cancer, or earlier tumor stage, when compared to tumors with MMR protein-positive expression.…”
Section: Discussionsupporting
confidence: 69%
“…As seen in other studies [4, 15, 37, 56, 67, 93, 94, 100–102], colorectal tumors with lack of MMR protein expression, suggesting MMR deficiency, were associated with a proximal location in the colon and poor histological differentiation. However, opposing previous publications [4, 17, 19, 37, 55, 72, 79, 101–104], we did not observe associations of MMR protein-negative tumors with gender, earlier age at diagnosis of cancer, positive personal and family history of cancer, or earlier tumor stage, when compared to tumors with MMR protein-positive expression.…”
Section: Discussionsupporting
confidence: 69%
“…In a case-control analysis using only cases and matched controls recruited via the Northern UK case:control study 12,13 (detailed in Materials and Methods), the MLH1 293A allele was not associated with an elevated risk of CRC independent of tumour site (GA 1 AA vs GG, OR 5 1.13, 95% C.I. 0.84-1.53, p 5 0.43, n 5 366 cases and 589 controls (GG homozygotes (n 5 369), GA heterozygotes (n 5 196), AA homozygotes (n 5 24)).…”
Section: Resultsmentioning
confidence: 99%
“…These included 776 Caucasian individuals with CRC diagnosed in the north of the United Kingdom, which comprised 366 incident cases who participated in a case:control study 12,13 (DNA from 589 age-and sex-matched Caucasian controls were also available from this study); 233 patients who underwent surgery for CRC in South Yorkshire, UK; 31 patients with MMR deficient CRC from St. James's University Hospital (Leeds, UK); and 146 cases with CRC identified retrospectively from the pathology database at Sheffield Hallamshire Hospital (Sheffield, UK). For simplicity, in the present study, these 776 CRC cases are collectively referred to as the ''Northern UK'' cases (Table I).…”
Section: Patientsmentioning
confidence: 99%
“…34 Furthermore, IHC triage of women with endometrial cancer having at least one affected first-degree relative was reported to be the most cost-effective strategy to identify mutation carriers and to prevent colorectal cancer. 35 Because some highly penetrant MMR missense mutations are reported to present with immunonormal tumor profiles, [36][37][38][39][40][41] we believe that IHC testing should support but not supplant the role of family history records in the detection of Lynch syndrome patients.…”
Section: Early Detection and Diagnosismentioning
confidence: 99%